The circadian clock component BMAL1 regulates osteogenesis in osseointegration - Deng, Shiyong; Qi, Meiyao; Gong, Ping; Tan, Zhen (Frontiers in Pediatrics, 2022)
Congenital and developmental craniofacial deformities often cause bone defects, misalignment, and soft tissue asymmetry, which can lead to facial function and morphologic abnormalities, especially among children born with cleft lip and palate. Joint efforts from oral maxillofacial surgery, oral implantology, and cosmetic surgery are often required for diagnosis and treatment. As one of the most widely performed treatment methods, implant-supported cranio-maxillofacial prostheses have been widely applied in the course of treatment. Therefore, stability of peri-implant bone tissue is crucial for the long-term success of treatment and patients’ quality of life. The circadian clock component brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein 1 (BMAL1) was found to be involved in the cell fate of bone marrow mesenchymal stem cells, which were essential in the fixation of titanium implants. This study aimed to investigate the effect of BMAL1 on osteogenesis in osseointegration, providing a brand new solution to increase bone implant conjunction efficiency and implant stability, paving the way for a long-term satisfactory therapy outcome.